Seroprevalence of HCMV among Pregnant Women and Its relation to CD4 and CRP - Mohammed Qader, Staar (Kurdistan Journal of Applied Research, 2018)
The HCMV is a widespread viral pathogen characterized by strict host specificity and is limited to humans. It has been described as an important etiological agent of intrauterine infection in during the pregnancy, which may lead to some serious results such as miscarriage, cerebellar malformation stillbirth, and fetus developmental retardation. The study carried out in Kirkuk governorate from the December 2017 to May 2018 for study the relation of CD4 percentage and CRP with HCMV seropositive pregnant women. The number of pregnant women under study was two hundred women attending to some private medical laboratories in Kirkuk. The pregnant women were examined for the seroprevalence of HCMV IgM and IgG antibodies by using VIDAS technique. The results were (81 %), (9%) and (6%) for HCMV-IgG, HCMV-IgM and for both IgG & IgM at the same time respectively. The highest rates (41.66%) of decreased CD4 percentage were within seropositive pregnant women for both IgG & IgM at same time, while the highest rates (16.66%)of CRP positive were found within HCMV-IgM seropositive group.